Tafsir Maqasidi Muhammad Talbi dan Abdul Mustaqim sebagai Pendekatan Alternatif dalam Menafsirkan Al-Qur’an - Iqbal Kholidi (ejournal.nurulqadim.ac.id, 2024)
Because the Qur'an is authentic in every era, the Qur'an should be interpreted appropriately according to the demands of life. Basically, life has changed in various situations and conditions, including lifestyle, human relations, globalization, migration, advances in technology and knowledge. Modernization has raised serious problems regarding the Koran as the main source of Islamic jurisprudence which appears